Analysis of Oil Palm Seedling Farming Bussiness (Case Study of Tridian Nursery and Sumber Makmur) - Tridio Saputra, Rahmad; HD, Ernawati; Yanita, Mirawati (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
This research aims to 1) describe the oil palm nursery farming business Tridian Nursery IPN and Sumber Makmur 2) analyze the income of the oil palm nursery farming business Tridian Nursery IPN and Sumber Makmur in Batanghari Regency, 3) Analyze the difference in the income of the oil palm nursery farming business Tridian Nursery IPN and Sumber Makmur. The analytical method used in this research is farming income analysis. The data source used in this research is primary data which is the result of interviews and questionnaires obtained from respondents using the purposive sampling method. The results of this research are 1) Tridian Nursery IPN and Sumber Makmur oil palm nursery farming uses a double stage nursery method consisting of pre nursery and main nursery, the main difference between Tridian Nursery and Sumber Makmur oil palm nurseries lies in the pre nursery stage which is IPN technology-based oil palm nurseries use temperature control devices so that the plants inside can grow at optimal temperatures. 2) Tridian Nursery IPN's oil palm nursery farming income is IDR. 109,527,333.33 while Sumber Makmur's palm oil income is Rp. 63,367,533.33 3) The difference in income from the Tridian Nursery and Sumber Makmur nursery farms is due to the fact that the amount of production from the Tridian Nursery nursery is greater, namely 5,200 stems compared to the production output from the Sumber Makmur nursery which is 4,550 stems, in addition to the selling price of Tridian Nursery oil palm seedlings IPN is greater than RP. 45,000 per stem while the selling price of Sumber Makmur nursery seeds is Rp. 40,000 per stem.